DISEMINASI PENGETAHUAN TOKOH KI NARTOSABDHO MELALUI EVENT FESTIVAL SEABAD NADA DAN WARISAN KI NARTOSABDHO KEPADA PEGIAT SENI MAHASISWA DI KOTA SEMARANG SEBAGAI ACCOUNT EXECUTIVE DAN EVENT MANAGER - Evania Angel Callista; S. Rouli Manalu (Interaksi Online, 2026)
TThe low level of knowledge among young art enthusiasts regarding the figure of Ki Nartosabdho has become a significant challenge in preserving Javanese arts in Semarang. Although interest in Javanese culture remains relatively high, understanding of his figure, works, and contributions is still limited. Therefore, this project aims to enhance the knowledge and understanding of young art communities in Semarang regarding the works and cultural legacy of Ki Nartosabdho through the organization of a cultural event titled “Festival Seabad Nada dan Warisan Ki Nartosabdho.” The conceptual framework applied is Integrated Marketing Communication (IMC), which integrates communication strategies through advertising, public relations and publicity, as well as events and experiences. The method used is an implementation-based approach through the design and execution of a cultural festival involving various university art student organizations (UKM) in Semarang, with a series of activities including art performances, multimedia exhibitions, cultural discussions, and collaborative performances. The author served as an Account Executive and Event Manager throughout the planning and implementation stages. The results indicate an increase in youth participation in art activities themed around Ki Nartosabdho, as well as improved audience understanding of his works and contributions, thereby strengthening the dissemination of cultural knowledge and fostering collaborative spaces among student art communities in Semarang